An Examination Of The Impact Of Strategic Planning Programs And Strategic Planning On Business Outcomes In China - Zhenhua, Zhong; Abbas Ali, Dhakir (Journal of Neonatal Surgery, 2025)
This dissertation delves at the link between the well-established ideas of strategic planning and strategic management, as well as the business schools that prioritize strategic planning. When examining the theoretical underpinnings of strategic management, the phrase "strategic administration school" is often used to describe the dominant paradigm held by the majority of senior-level executives. Strategic thinking, an essential but understudied talent, is the bedrock of strategic management. At the very top of an organization, only strategy will do. The mental process of "strategic thinking" defies easy classification, evaluation, or instruction due to its abstract nature. Three key features of strategic thinking have been found by empirical research: HEAR, FIRM, and PORT. The two most successful methods for encouraging strategic thinking in big Croatian companies, according to ROA and ROI studies, are FIRM and HEAR. The Resource-Oriented Approach and the Environmental Approach are two pillars of the Competitive-Contemporary school of thinking in strategic management operations. When it comes to return on equity (ROE), HEAR is good, PORT is bad, and FIRM is indifferent. Although conventional strategic management does not affect return on equity (ROE), environmental and competitive-contemporary schools do. Academics claim that people only utilize three of their five senses, thus we miss the screams for aid about the absence of a standardized, regulated framework for management, especially in strategic management.